THE SPECTROPHOTOMETRIC ANALYSIS OF PIGMENTS OF ALGA $CHLORELLA~PYRENOIDOSA$, SUBJECTED TO ACTION OF INCREASED TEMPERATURES (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
For an evaluation of a functional state of the photosynthetic apparatus investigated the effect of high temperatures on pigments system Chlorella pyrenoidosa. It is established, that under action of temperatures the contents of pigments decreases. Chlorophyll a and carotenoids are more sensitive. Concentration of chlorophyll b changes insignificantly, that testifies the stability of lightharvesting complex LHC (in fact all chlorophyll b is in LHC).
Keywords: $Chlorella~pyrenoidosa$; chlorophyll; contents of pigments; high temperatures